Kształtowanie się świadomości regionalnej mieszkańców województwa lubuskiego = Shaping of the regional awareness of the inhabitants of the Lubuskie province - Miszewski, Dariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The Lubuskie land was connected to Poland probably in the sixties of the tenth century, during the time of fights between Mieszko I and Wieleci tribes. They were fighting for domination in West Pomerania. The people of Lubuskie were probably part of Wieleci tribes and their land was situated on both riversides of the middle Odra. This area had strategic meaning for Poland at that time. Boleslaus III the Wrymouth found a bishopric in the Lubuskie land in 1124-1125, for the Christianization of West Pomerania. After his death, the Lubuskie land was attached to Silesia even though it was more important for Wielkopolska. The land was then connected to Brandenburg in 1252, after a civil war between the princes of Silesia.
Keywords: Ziemia Lubuska; historia; świadomość regionalna